(untitled) (Baghdad Science Journal, 2025)
Some of the characters of the Staphylolysin A and D enzymes purified from Pseudomonas aeruginosa P16 and P5 respectively were studied, the molecular weights of Staphylolysin A and D were 20.417 kilo dalton and 23.988 kilo Dalton respectively by SDS- polyacryl amide gel electrophoresis. The optimum pH for staphylolysin A activity was found to be 8 which gives higher activity reaches 150 unit/ml, and for enzyme stability was 7.5-8.5 in which the enzyme nearly retained its full activity, while it was 9.5 for staphylolysin D that gives higher activity of 16 unit/ml,and 8.5-9.5 for enzyme stability in which the enzyme nearly retained its full activity, Maximum activity of two enzymes was obtained at 40C in which the specific activity for staphylolysin A and D were 140 and 16.4 unit/ml, and the two enzymes remained approximately without change at 25-40C for one hour. When the effects of some materials on Staphylolysin A&D activity were studied, the results showed that both sodium chloride & potassium chloride at 1 & 5 mM had the activator effect on enzymatic activity compared with its control where the staphylolysin A and D retained 105% ,108% and 102%, 104% of their activity respectively when treated with sodium chloride, while they retained 110%, 114% and 133%, 118% of their activity respectively when treated with potassium chloride. The enzymatic activity for both enzymes were inhibited when treated with ferric , mercury and zinc chloride at variable ratios, Staphylolysin A kept 73% and 7% of its initial activity respectively when treated with 5mM of ferric chloride and mercury chloride respectively and it kept only 9% of its initial activity when treated with 0.1mM Zinc chloride . Staphylolysin D kept 45% and 13% of it is initial activity respectively when treated with 5mM of ferric chloride and mercury chloride respectively and it kept only 23% of its initial activity when treated with 0.1mM Zinc chloride while enzymatic activity for both enzymes were not affected when treated with EDTA at l0mM and phenyl methyl sulphonyl fluoride (PMSF) at 0.4mM.These results referred to that Staphylolysin A and D are Zn -metallo endopeptidase .